Hopper : all the best things about Belgian beers - Vandensteen, J. (Vilvoorde : Van Muuren, 2013)
The hopper ingedrients - Green gold - A beastly passion - The secret of Orval - Chees & Beer - Chef Kwinten De Paepe - Taste list - Duvel - The Pro League - Brussels City of Beer - Farm Brewerey - Pfophet abroad - Hoppert bits